The Effects of Permanent Income Tax Cuts on Emigration from Israel - Tomer Blumkin; Yoram Margalioth; Michel Strawczynski (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we introduce an analytical framework for analyzing the effect of permanent income tax reductions on emigration and conduct an empirical analysis of their impact, based on the Israeli tax reductions during 2004-2010. We find that permanent tax reductions reduce the emigration flows from Israel. According to our findings, this effect is stronger for workers in the low-tech sector than for their high-tech counterparts, as the former appear to be more sensitive to changes in net wages. Moreover, the effect is stronger for younger workers who benefit from permanent tax reductions for a longer period during their careers, relative to older workers.
Keywords: H20; J38; J61; 330; permanent tax cut; emigration